Religion and Violence: Unraveling Ahmad Syafii Maarif’s Philosophical Thought on the Muslim Community’s Internal Conflict - Taufani Taufani; Juhansar Juhansar; Hengki Firmanda (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2023)
This article outlines the philosophical view of Ahmad Syafii Maarif (ASM) in addressing internal conflicts within Muslims by tracing its root causes among Arab elites, starting from the time of the Prophet’s companions to inter-Arab conflicts in the contemporary era. This research is qualitative with a narrative approach using data from ASM’s writings and other related sources. The researchers collected, summarized, and presented data in a narrative format before concluding the data. Data analysis was conducted using Miles and Huberman’s thematic analysis technique. This article shows that the conflict among Muslims today, including in Indonesia, according to ASM, is the result of the legacy of conflict among Arab elites that began with the Prophet’s companions until the conflict between Arab nations in the contemporary era. The root of the problem in the conflict is the desire for political power by Arab elites. ASM’s post-Chicago studies resulted in substantial shifts in his attitude and philosophical perspective. He reevaluated the role of Islamic ethics in society concerning the concept of an Islamic state, encouraged interreligious tolerance among Muslims, questioned traditional female roles in Islam, and took a more critical stance toward sectarian differences within the faith. Indeed, ASM’s thought is supposed to be an alternative for resolving the internal conflict among Muslims worldwide.